Human liver stem cells and derived extracellular vesicles protect from sepsis-induced acute lung injury and restore bone marrow myelopoiesis in a murine model of sepsis - Andrea Costamagna; Chiara Pasquino; Sara Lamorte; Victor Navarro-Tableros; Luisa Delsedime; Vito Fanelli; Giovanni Camussi; Lorenzo Del Sorbo (Intensive Care Medicine Experimental)
Abstract Background Sepsis is a condition with high mortality and morbidity, characterized by deregulation of the immune response against the pathogen. Current treatment strategies rely mainly on antibiotics and supportive care. However, there is growing interest in exploring cell-based therapies as complementary approaches. Human liver stem cells (HLSCs) are pluripotent cells of mesenchymal origin, showing some advantages compared to mesenchymal stem cells in terms of immunomodulatory properties. HSLC-derived extracellular vesicles (EVs) exhibited a superior efficacy profile compared to cells due to their potential to get through biological barriers and possibly to avoid tumorigenicity and showed to be effective in vivo and ex vivo models of liver and kidney disease. The potential of HLSCs and their EVs in recovering damage to distal organs due to sepsis other than the kidney remains unknown. This study aimed to investigate the therapeutic potential of the intravenous administration of HSLCs or HSLCs-derived EVs in a murine model of sepsis. Results Sepsis was induced by caecal ligation and puncture (CLP) on C57/BL6 mice. After CLP, mice were assigned to receive either normal saline, HLSCs or their EVs and compared to a sham group which underwent only laparotomy. Survival, persistence of bacteraemia, lung function evaluation, histology and bone marrow analysis were performed. Administration of HLSCs or HLSC-EVs resulted in improved bacterial clearance and lung function in terms of lung elastance and oedema. Naïve murine hematopoietic progenitors in bone marrow were enhanced after treatment as well. Administration of HLSCs and HLSC-EVs after CLP to significantly improved survival. Conclusions Treatment with HLSCs or HLSC-derived EVs was effective in improving acute lung injury, dysmyelopoiesis and ultimately survival in this experimental murine model of lethal sepsis.